Inhibition of Human Tyrosinase Requires Molecular Motifs Distinctively Different from Mushroom Tyrosinase - Tobias Mann; Wolfram Gerwat; Jan Batzer; Kerstin Eggers; Cathrin Scherner; Horst Wenck; Franz Stäb; Vincent J. Hearing; Klaus‐Heinrich Röhm; Ludger Kolbe (2018)
Tyrosinase is the rate-limiting enzyme of melanin production and, accordingly, is the most prominent target for inhibiting hyperpigmentation. Numerous tyrosinase inhibitors have been identified, but most of those lack clinical efficacy because they were identified using mushroom tyrosinase as the target. Therefore, we used recombinant human tyrosinase to screen a library of 50,000 compounds and compared the active screening hits with well-known whitening ingredients. Hydroquinone and its derivative arbutin only weakly inhibited human tyrosinase with a half-maximal inhibitory concentration (IC50) in the millimolar range, and kojic acid showed a weak efficacy (IC50 > 500 μmol/L). The most potent inhibitors of human tyrosinase identified in this screen were resorcinyl-thiazole derivatives, especially the newly identified Thiamidol (Beiersdorf AG, Hamburg, Germany) (isobutylamido thiazolyl resorcinol), which had an IC50 of 1.1 μmol/L. In contrast, Thiamidol only weakly inhibited mushroom tyrosinase (IC50 = 108 μmol/L). In melanocyte cultures, Thiamidol strongly but reversibly inhibited melanin production (IC50 = 0.9 μmol/L), whereas hydroquinone irreversibly inhibited melanogenesis (IC50 = 16.3 μmol/L). Clinically, Thiamidol visibly reduced the appearance of age spots within 4 weeks, and after 12 weeks some age spots were indistinguishable from the normal adjacent skin. The full potential of Thiamidol to reduce hyperpigmentation of human skin needs to be explored in future studies.